Prevalence and concentration of specific antibiotic residues in raw milk from dairy farms in peri-urban Nairobi, Kenya - Wambua, C.N. (Moi University, 2016)
Background: Antibiotic residues in food are a public health concern globally. In Kenya, 86% of milk is consumed raw through informal markets, without quality check. We determined the prevalence of specific types of antibiotic residues in milk in dairy farms in a peri urban area. We compared their concentration with set maximum residue limits (MRLs). Methods: We conducted a cross sectional study in Uthiru between February and April 2016. Systematic sampling was used for farms and balloting to select three lactating cows. Data was collect using open data kit (ODK) and analyzed using Ms Excel and Epi Info. Screening was done using Charm Blue Yellow Test and High Performance Liquid Chromatography (HPLC) for identification of antibiotics and their concentrations Results: Out of 139 milk samples from 87 farms, overall antibiotic residue prevalence was 26.6 % (37/139; 95%CI: 19.2-34.1) on Charm Blue Yellow and 19.6 % (27/139; 95%CI: 13.3-27.2) on HPLC. Of the 37 positive samples, 16 (43.2%) were Sulphonamides, six (16.2%) were Tetracyclines, five (13.5%) were beta lactams, and the remaining ten (27.1%) could not be identified. Among the 16 Sulphonamides, the majority, 14 (75%) were Sulfadimethoxine, among the six Tetracyclines, all were Doxycycline, and among the five beta lactams, the majority 2 (40%) were Amoxicillin. The concentrations of antibiotic residues were higher 97% (26/27) than set MRLs. Conclusion: Antibiotic residues are prevalent in Uthiru with Sulphonamides residues being dominant. Residues were higher than set Maximum Residues Limits. We recommend regular checks by the Dairy Board of Kenya to trace antibiotic residues at farms.